Digitalisasi Administrasi Madrasah: Pengaruhnya Terhadap Kepuasan Layanan Guru - Mustaqim, Mustaqim; Khairunnisa, Risma (JURNAL MANAJEMEN PENDIDIKAN, 2025)
DIGITALIZATION OF MADRASAH ADMINISTRATION: ITS IMPACT ON TEACHER SERVICE SATISFACTIONThis research is motivated by the importance of digital transformation in the educational administration system, especially in improving the efficiency and quality of administrative services to educators. However, its implementation has not been entirely smooth, as some teachers still face difficulties in adapting to the digital systems in use. This study aims to measure the level of teachers’ satisfaction with administrative services and to analyze the relationship between administrative digitalization and the level of satisfaction with those services. The research employed a quantitative approach with a correlational method. The sample consisted of 75 teachers from MAN 1 Bandung City, selected using a simple random sampling technique. The research instrument was a four-point Likert scale questionnaire, which was tested through reliability, normality, linearity, Pearson correlation, and coefficient of determination analyses.The findings of the study highlight two key points. First, the level of teachers’ satisfaction with administrative services falls into the “high” category, with an average score of 3.31 on the Likert scale. Second, the correlation analysis indicates a very strong and significant relationship between administrative digitalization and teachers’ satisfaction with administrative services, with a correlation coefficient of 0.879 and a significance value of 0.000 0.05. Furthermore, the coefficient of determination (R²) of 0.772 shows that administrative digitalization contributes 77.2% to teachers’ satisfaction with administrative services, while the remaining 22.8% is influenced by other factors beyond the scope of this study..